Exploring the Islamic perspective on tissue engineering principles and practice - Sha'ban, Munirah; Zainuddin, Zainul Ibrahim; Abdul Rahman, Rozlin; Mohamad, Mohd Yusof; Mohamad Sukri, Norhamiza; Md Nazir, Noorhidayah; Ahmad Radzi, Muhammad Aa'zamuddin (2014)
Tissue engineering is related to the replacement, restoration, repair and/or regeneration of tissues and organs that are tailored to the needs of the individual patient. The potential applications of tissue engineering, both for clinical and non-clinical purposes are being unveiled with much hype and expectations among the scientists and the public at large. The demand for engineered tissues may increase considerably, but the progress has been slow due to scientific and technical challenges that closely linked to moral, religious, philosophical, political and economic aspects. There are on-going debates on certain aspects in tissue engineering that seem to indicate that scientists maybe “playing God”. This article briefly analyses and addresses tissue engineering principles and the discourse surrounding it. Subsequently, the author briefly reflects on the Islamic perspectives, both for and against tissue engineering, in the context of its principles and practices. The discussions are based on the concept of ijtihad that offers flexibility to examine and adopt new scientific developments and resolve issues in light of the Qurʼan and Sunnah. It serves to provide a platform on how best to achieve a consensus that adequately deals with the scientific reality and the Islamic moral and legal jurisprudence that surrounds the technology.